Description of the Level of Knowledge of Diabetes Mellitus Patients about Gymastics in Neighborhood Unit 01 Community Unit 01 Kebonsari Village Candi Subdistrict - Evi Dwi Kurnia Putri; Moch. Bahrudin; Luluk Widarti; Dony Sulystiono (Global Ten Public Health and Nursing Journal, 2025)
As a chronic condition that affects the body's glucose metabolism, diabetes mellitus requires comprehensive treatment, including gymnastics. It has been proven that gymnastics, as a nonpharmacological therapy, can help people with diabetes mellitus control blood sugar levels and improve quality of life. The purpose of this study was to determine the level of knowledge of patients with diabetes mellitus about gymnastics in Neighborhood Unit 01 Community Unit 01 Kebonsari Village Candi Subdistrict. Eleven respondents with varying age and gender participated in a descriptive study with a cross-sectional design. A questionnaire measuring the level of knowledge of gymnastics among diabetes mellitus patients in Neighborhood Unit 01 Community Unit 01 Kebonsari Village Candi Subdistrict, was used to collect data. 45.5% knew the definition of gymnastics. 100.0% knew the purpose of gymnastics. 72.7% knew the benefits of gymnastics. 72.7% know the types of gymnastics. 27.3% know the frequency of gymnastics. 63.6% know the duration of gymnastics. 54.5% know the intensity of gymnastics. 54.5% know the preparation for gymnastics. 54.5% know the factors that must be considered before gymnastics. 18.2% knew the use of footwear. Given the findings that a large number of respondents continued to choose the wrong answers, this study suggests a comprehensive strategy that incorporates organized instruction using accessible media of all ages.